Virulence Determinants of Acinetobacter baumannii Isolated from Different Infections in Baghdad Hospitals - Sajad Numan; Fitua Al-Saedi; Israa Burhan; Mojtaba Mohammadzadeh Vazifeh (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2024)
Acinetobacter baumannii is an essential pathogenic bacteria cause nosocomial infections worldwide. The current work aimed to characterize several virulence factors in Acintobacter baumannii isolated from diverse clinical specimens in Baghdad.